(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Disasters do not discriminate it affect across all sectors equally when strike. School children are one such vulnerable sections of society who got constantly hit by the adverse impact of disasters especially when they are in schools as it is one of the most densely populated place during day time. Some of the international forum vehemently emphasized upon safety of community in view of increasing risk of most vulnerable section of society. The Hyogo Framework for Action 2005-2015 Building the Resilience of Nations and Communities to Disasters, adopted at the World Conference on Disaster Reduction, highlights knowledge and education as one of the five main priorities of action. Attention was accorded and support given to efforts targeting school children and youth with the aim of making people more aware of the threat of hazards and of the need and possibility to become better prepared before disasters strike. Millennium Development Goal-2 indicate about ensuring universal and primary education but it has often notices that Disaster-hit families fail to send children to school, while schools may be closed down by earthquakes or floods. Sustainable Development Goal -4 also ensure inclusive and equitable quality education and promote lifelong learning opportunity for all but Disaster often hit education infrastructure and children often denied education during disaster phase and also post disaster phase be it natural or man-made disaster. Thus, an holistic integrated attention must be provided for mainstreaming Disaster Risk Reduction in education sector so that a safe learning environment may be provided to all the school going students.